Public health relevance of medicines developed under paediatric legislation in Europe and the USA: a systematic mapping study - Volodina, Anna; Jahn, Albrecht; Jahn, Rosa (BMJ paediatrics open, 2024)
Background Legislation in the European Union (EU) and the USA promoting the development of paediatric medicines has contributed to new treatments for children. This study explores how such legislation responds to paediatric health needs in different country settings and globally, and whether it should be considered for wider implementation. - Methods We searched EU and US regulatory databases for medicines with approved indications resulting from completed paediatric development between 2007 and 2018. Of 195 medicines identified, 187 could be systematically mapped to the burden of the target disease for six study countries (Australia, Brazil, Canada, Kenya, Russia, South Africa) and globally, using disability-adjusted life years (DALYs). All medicines were also screened for inclusion on the WHO Model List of Essential Medicines (EML) and the EML for children under 13 years (EMLc). - Results The studied medicines were disproportionately focused on non-communicable diseases, which represented 68% of medicines and 21% of global paediatric DALYs. On the other hand, we found 28% of medicines for communicable, maternal, neonatal and nutritional disorders, representing 73% of global paediatric DALYs. Neonatal disorders and malaria were mapped with two medicines, tuberculosis and neglected tropical diseases with none. The gap between medicines and paediatric DALYs was greater in countries with lower income. Still, 34% of medicines are included in the EMLc and 48% in the EML. - Conclusions Paediatric policies in the EU and the USA are only partially responsive to paediatric health needs. To be considered for wider implementation, paediatric incentives and obligations should be more targeted towards paediatric health needs. International harmonisation of legislation and alignment with global research priorities could further strengthen its impact on child health and support ongoing efforts to improve access to medicines. Furthermore, efforts should be made to ensure global access to authorised paediatric medicines.
Gesehen am 03.06.2024